Voltage quality in electrical power systems - Schlabbach, J. (Institution of Electrical Engineers, 2001)
Problems of voltage quality are becoming increasingly important with the growth in power electronics and the high-sensitivity of electronic equipment. Translated and updated from the German original published by VDE-Verlag, this volume details the theoretical background to low-voltage conducted disturbances in relation to voltage quality. The text describes solutions to practical application problems, including measurement, assessment and countermeasures, set in the context of European standards.
Includes index.
Keywords: Voltage regulators.; Electric power systems -- Quality control.; Electric power system stability.; elektronické knihy; electronic books